2015
DOI: 10.1007/s10955-015-1253-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Mechanics of the US Supreme Court

Abstract: We build simple models for the distribution of voting patterns in a group, using the Supreme Court of the United States as an example. The least structured, or maximum entropy, model that is consistent with the observed pairwise correlations among justices' votes is equivalent to an Ising spin glass. While all correlations (perhaps surprisingly) are positive, the effective pairwise interactions in the spin glass model have both signs, recovering some of our intuition that justices on opposite sides of the ideo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 27 publications
(36 reference statements)
0
89
0
Order By: Relevance
“…In fact, it has been shown that pairwise maximum entropy models (i.e., k 0 = 2) can provide an accurate description of the statistics of many biological systems [19][20][21][22] and also some social organizations [23,24].…”
Section: Negentropy and Total Correlationmentioning
confidence: 99%
“…In fact, it has been shown that pairwise maximum entropy models (i.e., k 0 = 2) can provide an accurate description of the statistics of many biological systems [19][20][21][22] and also some social organizations [23,24].…”
Section: Negentropy and Total Correlationmentioning
confidence: 99%
“…The couplings for the MVM indicate that all R's tend to vote with M (agreement between M and R leads to an increase in the log-probability ln r(s M = s R ) ∝ J MR as in Figure 1B) with a slight tendency for R's to disagree with each other more than would be expected given their shared correlation with M (disagreement between Ri and Rj decreases the log-probability of the vote by ln r(s R i = s R j ) ∝ J RR ). In principle, any probabilistic graph model is a viable alternative for the approach we outline, but the pairwise maxent model has been shown to capture voting statistics better than other models of voting with surprisingly few parameters (21,22), fits the data well (SI Appendix B), and presents a particularly / Z (A) Taking the pairwise correlations ( s R i s R j = 0 is not shown), (B) we solve a pairwise maxent model to learn the probability distribution p(s; {Jij}) parameterized by the couplings Jij. MVMs of different sizes N correspond to different coordinates in this two-dimensional space, but we focus on N = 7 as an example.…”
Section: Median Voter Model (Mvm)mentioning
confidence: 99%
“…(2), which is the maximum entropy model [31][32][33], analogous to the Ising model. We thus interpret the dependent variable as an "energy", noting that the logarithm of the solubility is proportional to the solvation energy.…”
mentioning
confidence: 99%